DNA methylation‐mediated silencing of microRNA‐204 enhances T cell acute lymphoblastic leukemia by up‐regulating MMP‐2 and MMP‐9 via NF‐κB. Issue 5 (10th February 2021) - Lin, Congmeng; Chen, Dabing; Xiao, Tingting; Lin, Dandan; Lin, Dayi; Lin, Luhui; Zhu, Haojie; Xu, Jingjing; Huang, Wenwen; Yang, Ting
Abstract: T cell acute lymphoblastic leukaemia (T‐ALL) is a highly aggressive haematological cancer of the bone marrow. The abnormal expression of microRNAs (miRNAs) is reportedly involved in T‐ALL development and progression. Thus, we aimed to decipher the involvement of miR‐204 silencing mediated by DNA methylation in the occurrence of T cell acute lymphoblastic leukaemia (T‐ALL). miR‐204 expression was determined in bone marrow and peripheral blood samples from T‐ALL patients by real‐time quantitative PCR (RT‐qPCR) with its effect on cell proliferation evaluated by functional assays. In addition, bisulphite sequencing PCR was employed to detect the DNA methylation level of the miR‐204 promoter region, and the binding site between miR‐204 and IRAK1 was detected by luciferase assay. We found that miR‐204 was down‐regulated in T cells of T‐ALL patients, which was caused by the increased DNA methylation in the promoter region of miR‐204. Moreover, overexpression of miR‐204 inhibited T‐ALL cell proliferation while enhancing their apoptosis through interleukin receptor‐associated kinase 1 (IRAK1), which enhanced the expression of matrix metalloproteinase‐2 (MMP‐2) and MMP‐9 through activation of p‐p65. Thus, miR‐204 modulated MMP‐2 and MMP‐9 through IRAK1/NF‐κB signalling pathway, which was confirmed by in vivo assay. Taken together, DNA methylation‐mediated miR‐204 silencing increased the transcription of IRAK1, thus activating the NF‐κB signalling pathway and up‐regulating the downstream targets MMP‐2/MMP‐9.